KAJIAN TENTANG PROSES PENANGANAN TINDAK PIDANA PEMBUNUHAN OLEH ORANG DENGAN GANGGUAN KEJIWAAN (STUDI KASUS DI POLRES TIMUR TENGAH SELATAN) - Adipura Alden Putra Banfatin; Bhisa Vhitus Wihelminus; Orpa Ganefo Manuain; Deddy R.Ch. Manafe (PT. Hasba Edukasi Mandiri, 2026)
Murder is one of the most serious crimes against life, carrying significant legal, social, and humanitarian consequences. Legal issues become more complex when the perpetrator is a Person with Mental Disorders (ODGJ), as the individual's mental condition may affect the capacity to understand and be held criminally responsible for the act committed. Under Article 44 of the Indonesian Criminal Code (KUHP), a person who commits a criminal act while suffering from a mental disorder cannot be punished if it is proven that they are incapable of being held responsible for their actions. This study aims to analyze the legal considerations underlying the decision of the Timor Tengah Selatan Regional Police to terminate the investigation of a murder case committed by a person with mental disorders and to examine the legal handling process applied to such offenders. This research employs an empirical legal method with a case approach. Data were collected through interviews with investigators and related parties at the Timor Tengah Selatan Regional Police and through a literature review of legislation, legal doctrines, and supporting documents. The data were analyzed qualitatively by correlating empirical findings with applicable legal provisions. The findings reveal that the termination of the investigation was based on Article 44 of the Indonesian Criminal Code, Article 109 paragraph (2) of the Criminal Procedure Code (KUHAP), Regulation of the Chief of Police Number 6 of 2019 concerning Criminal Investigations, and psychological examination results indicating that the offender suffered from a mental disorder and was therefore incapable of criminal responsibility. The legal handling process included preliminary investigation, formal investigation, witness examination, evidence collection, psychiatric assessment, case review, issuance of an Order for Termination of Investigation (SP3), and recommendations for medical rehabilitation. The study concludes that the handling of murder cases involving persons with mental disorders requires an integrated approach encompassing legal, medical, and humanitarian perspectives to ensure legal certainty, substantive justice, protection of human rights, and recovery of the offender’s mental condition. These findings highlight the importance of coordination among law enforcement agencies, mental health professionals, prosecutors, and the offender’s family in managing criminal cases involving persons with mental disorders in a professional and equitable manner.